Effects of Doping Concentration and Emission Layer Thickness on Recombination Zone and Exciton Density Control in Blue Phosphorescent Organic Light-Emitting Diodes. (1st January 2017) - Jesuraj, P. Justin; Hafeez, Hassan; Rhee, Sang Ho; Kim, Dong Hyun; Song, Myungkwan; Kim, Chang Su; Ryu, Seung Yoon
Abstract : Herein, we evaluate the effects of the doping concentration and emissive layer (EML) thickness to control the recombination zone (RZ) and exciton density (ED) in blue phosphorescent organic light-emitting diodes (Ph-OLEDs). Varying the doping concentration of the guest molecule iridium-(III)-bis-[(4, 6-difluorophenyl)-pyridinato-N, C2'] picolinate (FIrpic) in host materials together with different EML thicknesses induced a change in the RZ and ED and also influenced the quenching of triplet excitons. Increasing the dopant concentration in the 20 nm EML generated a wider RZ and greater ED and induced a blueshift in the electroluminescence spectrum, whereas a redshift in the electroluminescence (EL) spectrum was observed in the case of the 30 nm EML. It is proposed that the micro-cavity effect (around 500 nm), shift of the RZ and ED along with band alignment tactics were operative for improving the performance of the blue Ph-OLEDs.